A discursivização do trabalho no Jardim Botânico de Porto Alegre : turismo, sujeito e sentidos - Souza, Denise de (My University, 2016)
This research analyzes relations between Tourism, Subject and Work from the perspective of the gardeners of the Porto Alegre Botanical Garden. The research investigates the worker's position relating to tourism, and the botanical gardens as places of opportunity for leisure. The concept of work in this study is the same concept of the theory of Psychodynamics Of Work, dejourian approach.The concepts of the French Discourse Analysis of Pêcheux are the methodological support of research. The construction of the analysis was done by extraction of discursive sequences from interviews and notes in field diary. The survey results identified and located the discrepancy between prescribed work and real work of the gardeners. The concept of the Discursive Formation showed alliances and confrontations in rearrangements of Work Organization articulated by these workers. The relationship between the visitor, tourist citizen, and the gardener worker shows up significantly because it is based on the recognition of the originality and usefulness of the gardener's work, condition for pleasure at work and mental health of the worker.
Esta pesquisa analisa as relações entre Turismo, Sujeito e Trabalho, sob a perspectiva dos jardineiros, no espaço do Jardim Botânico de Porto Alegre. A investigação deu-se a partir da posição do trabalhador no campo de atividade turística, e dos jardins como locais de possibilidade para o lazer. O conceito de trabalho tomado para esse estudo é o da Psicodinâmica do Trabalho, de abordagem dejouriana. O suporte metodológico é oferecido pelos conceitos da Análise de Discurso Francesa pecheutiana. A construção analítica se viabiliza através da extração de sequências discursivas das entrevistas e das anotações em Diário de Campo. Os resultados da pesquisa identificaram e situaram a defasagem entre o trabalho prescrito e o trabalho real dos jardineiros. O conceito de Formação Discursiva permitiu observar alianças e confrontos nos rearranjos da Organização do Trabalho, articulados por esses trabalhadores. A relação entre o visitante, turista cidadão, e o trabalhador jardineiro mostrou-se significativa, pois está ancorada no reconhecimento da originalidade e utilidade do trabalho do jardineiro, condição para o prazer no trabalho e para a saúde mental do trabalhador.
Keywords: Jardim Botânico (Porto Alegre, RS); Turismo - Porto Alegre (RS); Análise do discurso; Trabalho - Aspectos psicológicos; Psicologia social; Tourist trade - Porto Alegre (Brazil); Botanical Garden (Porto Alegre, Brazil); Discourse analysis; Work - Psychological aspects; Social psychology